Ovarian tissue cryopreservation in the pediatric with rare diseases- experience from China’s first and the largest ovarian tissue cryobank - Ruan, Xiangyan; Cheng, Jiaojiao; Du, Juan; Jin, Fengyu; Gu, Muqing; Ju, Rui; Wu, Yurui; Li, Long; Wang, Yuejiao; Jiang, Lingling; Yang, Yu; Li, Yanqiu; et al. (Frontiers in Endocrinology, 2023)
Background: There is limited information about the efficacy of ovarian tissue cryopreservation (OTC) in children. In the present study, we report eight patients with rare diseases who underwent OTC in China's first and largest ovarian tissue cryobank. Procedure: Data from girls with rare diseases who underwent OTC between September 2020 and November 2022 were retrospectively analyzed. We also compared the number of cryopreserved cortex pieces, follicle number, and AMH in those with rare diseases and age-matched children with non-rare diseases who also underwent OTC in our cryobank. Results: The median age of the children was 5.88±3.52 (range 2-13) years old. Unilateral oophorectomy was undertaken via laparoscopy in all of the children. The diseases in the 8 patients were: 4 mucopolysaccharidoses (MPS I two cases, IVA two cases)，1 Diamond-Blackfan anemia (DBA), 1 Fanconi anemia (FA), 1 hyperimmunoglobulin E syndrome (HIES), 1 Niemann-Pick disease. The number of cryopreserved cortex pieces was 17.13±6.36, and the follicle count per 2 mm biopsy was 447.38±524.35. No significant difference in age, the count of cryopreserved cortex pieces, follicle number per 2 mm biopsy, and AMH level was seen between the 20 children with non-rare diseases and those with rare diseases. Conclusions: The reports help practitioners counsel girls with rare diseases about fertility preservation. The demand for OTC in pediatrics will likely grow as a standard of care.